Manual of dietetic practice - Gandy, Joan; British Dietetic Association (Hoboken, NJ : John Wiley & Sons, Inc. : The British Dietetic Association, 2019)
Manual of Dietetic Practice (6th Edition, ISBN 9781119235927) is the authoritative guide for dietetic students and experienced practitioners alike, fully endorsed by the British Dietetic Association. Thoroughly revised and updated in 2019, this comprehensive resource spans the entire dietetic curriculum$1 (Bcovering the latest scientific developments, nutrition surveillance data, evidence-based practice guidelines, insights into Public Health England$1 (Bs influence, public health intervention strategies, and a companion website with learning aids$1 (Bmaking it an indispensable reference for healthcare professionals and educators.s
Includes bibliographical references and index.
In English
NBL010825
Keywords: Diet Therapy; Dietetics; Nutritional Physiological Phenomena